2021
DOI: 10.3390/ani11102826
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Expression Profiles of CircRNA and MiRNA in Oviduct during the Follicular and Luteal Phases of Sheep with Two Fecundity (FecB Gene) Genotypes

Abstract: CircRNA and miRNA, as classes of non-coding RNA, have been found to play pivotal roles in sheep reproduction. There are many reports of circRNA and miRNA in the ovary and uterus, but few in the oviduct. In this study, RNA-Seq was performed to analyze the expression profile of circRNA and miRNA in the oviduct during the follicular phase and luteal phase of sheep with FecBBB and FecB++ genotypes. The results showed that a total of 3223 circRNAs and 148 miRNAs were identified. A total of 15 DE circRNAs and 40 DE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 89 publications
(90 reference statements)
1
5
0
Order By: Relevance
“…44 circRNAs were differentially expressed and majority of enriched GO terms of DECs host genes were related to cell proliferation and reproductive process and KEGG enrichment analysis enriched in cell adhesion molecules, phagosome, PI3K-Akt signaling pathway, neuroactive ligand-receptor interaction, glutathione metabolism, metabolism of xenobiotics by cytochrome P450, MAPK, axon guidance, valine, leucine and isoleucine degradation, and endocytosis pathways. A similar phenomenon was observed in other studies [ 27 , 28 , 32 ]. Metabolic changes reported during transition period from ovulation to the estrous and biomolecules including vitamins, amino acids, lipid, benzoic acid, carbohydrates and other intermediate and secondary metabolites are at their highest levels at the time of ovulation [ 27 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…44 circRNAs were differentially expressed and majority of enriched GO terms of DECs host genes were related to cell proliferation and reproductive process and KEGG enrichment analysis enriched in cell adhesion molecules, phagosome, PI3K-Akt signaling pathway, neuroactive ligand-receptor interaction, glutathione metabolism, metabolism of xenobiotics by cytochrome P450, MAPK, axon guidance, valine, leucine and isoleucine degradation, and endocytosis pathways. A similar phenomenon was observed in other studies [ 27 , 28 , 32 ]. Metabolic changes reported during transition period from ovulation to the estrous and biomolecules including vitamins, amino acids, lipid, benzoic acid, carbohydrates and other intermediate and secondary metabolites are at their highest levels at the time of ovulation [ 27 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 91%
“…In sheep uterus study, 147 and 364 circRNAs out of 32,687 were differentially expressed in polytocous and monotocous groups in the follicular phase and luteal phases and DECs host genes significantly enriched with estrogen signaling pathway, oxytocin signaling pathway [ 27 ]. While, in the comparative study between the follicular phase/luteal phase of sheep, 15 DECs out of 3223 were predicted and DECs host genes were enriched in the Rap1 signaling pathway, PI3K–Akt signaling pathway and neuroactive ligand–receptor interactions [ 28 ]. In this study, we found 9,878 new circRNAs with a total length of 23522667nt and an average length of 2381.32nt respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…INHBB (inhibin beta B subunit) is a glycoprotein hormone that belongs to the transforming growth factor-β superfamily and inhibits follicle-stimulating hormone (FSH) production and secretion [ 27 ]. Knockdown of INHBB increases apoptosis and inhibits steroidogenesis in mouse granulosa cells [ 28 ], and the gene was also found to be closely associated with reproductive processes in sheep [ 29 ]. High expression of INHBB transcripts in the ovaries of WL hens may increase the apoptosis of granulosa cells, inhibit hormone production, and lead to lower egg production.…”
Section: Discussionmentioning
confidence: 99%